Contingent Systems Art and/as Algorithmic Critique. - SCARLETT, ASHLEY; LIPTON, LISA (Afterimage, 2023)
The article presents the discussion on critical intersections between creative practice and algorithmic culture. Topics include coupling of facial recognition technologies with machine learning being automating and expanding the efficacy of surveillance tactics; and gap in research and the need to further develop methods for algorithmic critique and possible resistance serves as the point of departure.